2020
DOI: 10.5194/acp-2019-1146
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Size-resolved aerosol pH over Europe during summer

Abstract: <p><strong>Abstract.</strong> The dependence of aerosol acidity on particle size, location and altitude over Europe during a summertime period is investigated using the hybrid version of aerosol dynamics in the chemical transport model PMCAMx. The pH changes more with particle size in northern and southern Europe owing to the enhanced presence of non-volatile cations (Na, Ca, K, Mg) in the larger particles. Differences of up to 1–4 pH units are predicted … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The pH calculated here is compared against pH estimations from field derived PM 2.5 compositional data around the world compiled by Pye et al (2020) (Table S1). pH data derived from other aerosol sizes (e.g., PM 1 ) has been omitted since aerosol acidity can vary significantly with size (Zakoura et al, 2020 in Table S1 aims to corroborate the spatial variability of pH found in this study and not to strictly evaluate the model calculations. Observationally estimated aerosol pH is derived from a variety of methods that can affect the result significantly as discussed above (i.e., the use of E-AIM or ISORROPIA, stable/metastable assumption, forward/reverse mode, and the availability of gas phase NH 3 /HNO 3 , crustal species, and organic aerosol water observations).…”
Section: Ph Calculationsmentioning
confidence: 99%
“…The pH calculated here is compared against pH estimations from field derived PM 2.5 compositional data around the world compiled by Pye et al (2020) (Table S1). pH data derived from other aerosol sizes (e.g., PM 1 ) has been omitted since aerosol acidity can vary significantly with size (Zakoura et al, 2020 in Table S1 aims to corroborate the spatial variability of pH found in this study and not to strictly evaluate the model calculations. Observationally estimated aerosol pH is derived from a variety of methods that can affect the result significantly as discussed above (i.e., the use of E-AIM or ISORROPIA, stable/metastable assumption, forward/reverse mode, and the availability of gas phase NH 3 /HNO 3 , crustal species, and organic aerosol water observations).…”
Section: Ph Calculationsmentioning
confidence: 99%
“…Dust particles chemically age in the atmosphere, getting coated by acids (such as sulphuric acid, nitric acid or chlorine), or organic species (Goodman et al, 2000). The uptake rates of such compounds on dust aerosols are enhanced by the amount of calcite and other alkaline components present (Krueger et al, 2004;Zakoura et al, 2020). Due to these coatings, originally hydrophobic dust becomes hygroscopic, which favors cloud formation processes (Usher et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Each method has different advantages and disadvantages (e.g., time resolution, sample preparation, range of species identified, cost, and personnel needs). These results, in turn, have been used to inform and improve the results of CTMs, influencing our understanding of processes such as the direct radiative effect (Wang et al, 2008b), transport of ammonia in deep convection (Ge et al, 2018), aerosol pH (Pye et al, 2020;Zakoura et al, 2020) and subsequent chemistry, and precursor emissions (Henze et al, 2009;Heald et al, 2012;Walker et al, 2012;Mezuman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%